Model Regresi Pengaruh Rasio Keuangan Terhadap Persentase Pendapatan Bersih Pada Perusahaan Ace Hardware Indonesia Tbk. - Utomo, Rukmono Budi (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
This paper describes a mathematical model of finance ratios against net income percentage in Indonesia Hardware Ace Company. This model constructed using multiple linear regression. In this paper, we used some financial ratios such as Current Ratio (CR), ROA, ROE, GPM, OPM, NPM, Payout Ratio, and Yield as ingredients to construct regression mathematics model. We use data from the Indonesia Hardware Ace company report in the year 2013 and 2014. This data available and can download any digital sources especially from Indonesia Capital Market Directory (ICMD). Data then processed using statistical software namely SPSS version 17.0 for helped us constructed a mathematical regression model. This research yields multiple regression model with value of . It means that the mathematical model very completed and useful to the application.Â Keyword:Â Finance Ratios, Net Income, Regression, ACE Hardware Indonesia